DIIA: Blockchain-Based Decentralized Infrastructure for Internet Accountability. (19th July 2021) - Li, Pengkun; Su, Jinshu; Wang, Xiaofeng; Xing, Qianqian
Abstract : The Internet lacking accountability suffers from IP address spoofing, prefix hijacking, and DDoS attacks. Global PKI-based accountable network involves harmful centralized authority abuse and complex certificate management. The inherently accountable network with self-certifying addresses is incompatible with the current Internet and faces the difficulty of revoking and updating keys. This study presents DIIA, a blockchain-based decentralized infrastructure to provide accountability for the current Internet. Specifically, DIIA designs a public-permissioned blockchain called TIPchain to act as a decentralized trust anchor, allowing cryptographic authentication of IP addresses without any global trusted authority. DIIA also proposes the revocable trustworthy IP address bound to the cryptographic key, which supports automatic key renewal and efficient key revocation and eliminates complexity certificate management. We present several security mechanisms based on DIIA to show how DIIA can help to enhance network layer security. We also implement a prototype system and experiment with real-world data. The results demonstrate the feasibility and suitability of our work in practice.